PENGARUH GADGET TERHADAP PERKEMBANGAN MORAL ANAK SD KELAS 3 DI SDN 06 PAGI KEBON JERUK - Martin, Riky; Halim, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is grounded in the findings of a preliminary study conducted on 3rd-grade students at SDN 06 Pagi Kebon Jeruk, revealing a high level of student attachment to their gadgets. This attachment carries the potential risk of gadget addiction, leading to psychological disturbances such as concentration problems, hyperactivity, and moral behavior issues in children. The primary aim of this study is to investigate the impact of gadget usage on the moral development of 3rd-grade elementary school students at SDN 06 Pagi Kebon Jeruk. The research employs a quantitative associative approach. The research population comprises 96 participants of third-grade students at Sekolah Dasar Negeri 06 Pagi Kebon Jeruk Jakarta Barat. In The sample in this study was selected using the total sampling technique.. Data were collected through a questionnaire instrument utilizing a Likert scale. The study reveals a significant positive influence of gadget usage on the moral development of children at Sekolah Dasar Negeri 06 Pagi Kebon Jeruk Jakarta Barat (sig p 0.044, with a simple linear regression equation Y= 32.954 -0.185X) and an R-square value of 0.43, indicating a 43% influence of gadget usage on child development. The remaining percentage is influenced by other variables or factors.